CitizenM’s South East Asia Market Entry Analysis - Sebastian Kornelius (iBuss Management, 2020)
The hospitality/tourism industry is one of the most growing and promising sectors in the world’s economy. Focusing the scope on the South East Asia (SEA) region, the region is considered as the largest tourism growth market and will bring a tremendous impact towards the region’s economy in the near future. This puts SEA in a favourable position for CitzenM to plan out its further expansion towards the region. This research will cover the analysis, strategy formulation and recommendations for the company to successfully penetrate the SEA region. External analysis (PESTEL Analysis) and internal analysis were utilized for both determining the specific potential market and competitive position of the company in the market. Further into the analysis, Porter’s Five Forces, 4C Marketing Mix and 4 Aspect of Service Marketing is used to analyse both the current industry situation within the market and narrowing down the company’s competitive advantages. Strategy formulation and recommendations are generated upon completing the analysis, and has been found that, cost leadership, partnering channels, direct entry mode, and social media influencer endorsement are necessary strategies for CitizenM to implement, in order to, secure its success in penetrating the market, which in return will increase its market share.Keywords: Hospitality Industry, Tourism Industry, Strategy Formulation, South East Asia Market, Market Penetration